Novel Air Stimulation MR-Device for Intraoral Quantitative Sensory Cold Testing - Brönnimann, Ben; Meier, Michael L.; Hou, Mei-Yin; Parkinson, Charles; Ettlin, Dominik A. (Frontiers in Human Neuroscience, 2016)
The advent of neuroimaging in dental research provides exciting opportunities for relating excitation of trigeminal neurons to human somatosensory perceptions. Cold air sensitivity is one of the most frequent causes of dental discomfort or pain. Up to date, devices capable of delivering controlled cold air in an MR-environment are unavailable for quantitative sensory testing. This study therefore aimed at constructing and evaluating a novel MR-compatible, computer-controlled cold air stimulation apparatus (CASA) that produces graded air puffs. CASA consisted of a multi-injector air jet delivery system, a cold exchanger, a cooling agent and a stimulus application construction. Its feasibility was tested by performing an fMRI stimulation experiment on a single subject experiencing dentine cold sensitivity. The novel device delivered repetitive, stable air stimuli ranging from room temperature (24.5 °C ± 2 °C) to -35° C, at flow rates between 5 and 17 liters per minute (l/min). These cold air puffs evoked perceptions similar to natural stimuli. Single-subject fMRI-analysis yielded brain activations typically associated with acute pain processing including thalamus, insular and cingulate cortices, somatosensory, cerebellar and frontal brain regions. Thus, the novel CASA allowed for controlled, repetitive quantitative sensory testing by using air stimuli at graded temperatures (room temperature down to –35 °C) while simultaneously recording brain responses. No MR-compatible stimulation device currently exists that is capable of providing non-contact natural-like stimuli at a wide temperature range to tissues in spatially restricted areas such as the mouth. The physical characteristics of this novel device thus holds promise for advancing the field of trigeminal and spinal somatosensory research, namely with respect to comparing therapeutic interventions for dentine hypersensitivity.